Cold-Formed Steel Truss Roof Structure Failure Considering Seismic Load and Buckling Analysis - Muslikh; Iman, Miftahul (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
There were many incidents of cold-formed steel roof truss structures in the last 5 years in Indonesia. Various kinds of allegations have been addressed to cold-formed steel material applications especially in the case of seismic resistance. Some of them concern the authenticity of the steel material itself and the selection of cold formed steel material. On the other hand, recently, people have installed (assembled) cold-formed steel trusses without involving a certified cold-formed steel applicator. This research is based on a numerical study that modeled the collapse pattern of cold-formed steel truss roof structures by considering buckling failure and the seismic load capacity. The cold-formed steel roof truss structure was modeled with 3D-truss elements in two model types: the overall structure and a single compression member element in 3D solid idealization. Buckling analysis with eigenvalue and nonlinear static analysis was performed to evaluate the critical load (Pcr). The buckling mode shape also was also compared with the mode shape of modal analysis. This research also evaluated the effect of seismic load on the overall cold-formed steel truss structure and the slenderness of the compression member. The numerical simulation of cyclic loading on the single compression member was conducted in this research. The numerical analysis results showed that cold-formed steel roof truss structure have high vulnerability to seismic hazard effect. The cold-formed steel material has lower ductility than hot rolled steel material. This causes the lateral displacement that occurs to be lower than the displacement produced by the hysteretic curve of numerical cyclic simulation. This research also evaluated the dynamic properties, such as frequency, periods, and mode shapes, of some typical cold-formed steel for roof truss structure.